2021
DOI: 10.3390/nu13041153
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Patterns with Weight Status and Metabolic Risk Factors among Children and Adolescents

Abstract: Unhealthy dietary patterns are associated with obesity in children and adolescents. However, few studies have investigated the relationships between dietary patterns and obesity-related metabolic disorders among Asians. We identified dietary patterns in children and adolescents and examined the associations between these patterns and obesity, insulin resistance, and metabolic syndrome in South Korea. This study is a cross-sectional design. We used baseline data from an intervention study of 435 Korean children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
1
8
0
1
Order By: Relevance
“…High sugar intake positively correlated with risk of diabetes in this present study. This has a general agreement with previous study that high sugar intake associated with diabetes, obesity, and other cardiovascular risks [ 11 , 31 ]. This present study also showed that high sugar intake did not correlated with the occurrence of insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…High sugar intake positively correlated with risk of diabetes in this present study. This has a general agreement with previous study that high sugar intake associated with diabetes, obesity, and other cardiovascular risks [ 11 , 31 ]. This present study also showed that high sugar intake did not correlated with the occurrence of insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies on associations between obesity and other cardiovascular disease risks and intake of fat and sugar and dietary fibre intake are conducted in high-income countries [ 9 , 11 , 12 ]. A recent published study evaluated fast food and soda pattern associated with significantly elevated insulin resistance among children and adolescents [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some previous studies analyzing the dietary patterns of children and adolescents have been conducted in Europe and Australia [ 10 , 23 , 24 ], in which a relationship between the Westernized dietary pattern and increased risk of MetS was observed. A study in Korea reported white rice and kimchi consuming were associated with lower weight and higher HDL cholesterol, and oil and seasoned vegetable consuming were significantly associated with a lower weight, WC, and serum insulin level, whereas fast-food and soda consuming correlated with higher WC, serum insulin and BMI [ 25 ].…”
Section: Discussionmentioning
confidence: 99%